Numerical Study of Fracture Characteristics of Deep Granite Induced by Blast Stress Wave. (15th September 2021) - Zhu, Zheming; Gao, Weiting; Wan, Duanying; Wang, Meng; Shu, Yun
Abstract : To study the characteristics of rock fracture in deep underground under blast loads, some numerical models were established in AUTODYN code. Weibull distribution was used to characterize the inhomogeneity of rock, and a linear equation of state was applied to describe the relation of pressure and volume of granite elements. A new stress initialization method based on explicit dynamic calculation was developed to get an accurate stress distribution near the borehole. Two types of in situ stress conditions were considered. The effect of heterogeneous characteristics of material on blast-induced granite fracture was investigated. The difference between 2D models and 3D models was discussed. Based on the numerical results, it can be concluded that the increase of the magnitude of initial pressure can change the mechanism of shear failure near the borehole and suppress radial cracks propagation. When initial lateral pressure is invariable, with initial vertical pressure rising, radial cracks along the acting direction of vertical pressure will be promoted, and radial cracks in other directions will be prevented. Heterogeneous characteristics of material have an obvious influence on the shear failure zones around the borehole.